2016
DOI: 10.1387/ijdb.160083yy
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes thyroid differentiation of native murine induced pluripotent stem cells

Abstract: Hypothyroidism is a very common hormonal deficiency and the stem cell technology which developed in the recent years may offer a therapeutic strategy for treating this disorder. Hypoxia has been demonstrated to play an important role in embryonic formation and development and to modulate stem cell differentiation. However, the influence of oxygen tension on thyroid differentiation has not been studied. In this study, we used murine induced pluripotent stem (iPS) cells for thyroid cell differentiation under nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…The study conducted by Liao et al (2012) showed that ROBO2 gene was downregulated by hypoxia in cells from placenta of pregnant women with preeclampsia and the authors reported that the deregulation of ROBO2 could impair placental development [ 36 ]. In the present study, other differentially methylated genes were found in the HbSC group, and some of them were also reported to be affected by hypoxia, including TGFB , IJAP1 and GATA4 [ 37 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…The study conducted by Liao et al (2012) showed that ROBO2 gene was downregulated by hypoxia in cells from placenta of pregnant women with preeclampsia and the authors reported that the deregulation of ROBO2 could impair placental development [ 36 ]. In the present study, other differentially methylated genes were found in the HbSC group, and some of them were also reported to be affected by hypoxia, including TGFB , IJAP1 and GATA4 [ 37 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…Thus, Ma Y. et al found that the effect of dosed hypoxia (5% O2) enhanced the synthesis of hypoxia-inducing factor which stimulated the synthesis of thyroid hormones [15]. An increase in the expression of transcription markers of thyroid hormones and an increase in the differentiation of the gland during hypoxia were shown [16].…”
Section: Discussionmentioning
confidence: 98%
“…[ 217 ] Additional optimization of the culture parameters could further promote the differentiation into thyroid tissues, since hypoxia (2% O 2 ) was reported to increase the expression of thyroid transcription factors (Pax8 and Nkx2.1), the expression of NIS and TSHR, and the uptake of iodide. [ 227 ]…”
Section: Human Organ Structure and Functions And Their Modeling In Vitromentioning
confidence: 99%
“…[217] Additional optimization of the culture parameters could further promote the differentiation into thyroid tissues, since hypoxia (2% O 2 ) was reported to increase the expression of thyroid transcription factors (Pax8 and Nkx2.1), the expression of NIS and TSHR, and the uptake of iodide. [227] Fewer efforts have been directed at developing 3D models for the initiating steps of the HPT axis within the hypothalamus and the pituitary. However, coinduction of hypothalamic and oral ectoderm from ESCs [228,229] and hiPSCs [230] facilitated the formation of 3D organoids with different hormone-producing pituitary cells adjacent to functional hypothalamic tissue.…”
Section: Thyroid Systemmentioning
confidence: 99%